Age-related changes in the immune system of growing rats under acute and chronic stress conditions - Kapitonova, Marina; Mansor, Othman; Ullah, Muzammil (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
Objectives : To examine whether or not excess pyruvate can provide the metabolic sub~trate to support the growth of early embryos in the presence of peritoneal fluid with endometriosis or interleukin- a . Introduction : The adverse effect of peritoneal fluid with endometriosis on .early embryo growth has previously been described (1). Recent studies suggest that interleukinsmay be the embryotoxic factor mediating the effect of endometriosis. This hypothesis is supported by the presence of interleukins in the peritoneal fluid obtained from women with endometriosis (unpublished observation). A common-metabolic pathway mediating the effects. of endometriosis and interleukin could provide further support to the hypothesis. · Methodology : Two-cell mouse embryos were cultured in 1 ml Whitten's medium as previously described (1). The effects of excess pyruvate (1 mmol) on early embryo growth in the presence of peritoneal fluid with endometriosis or interleukin-8 were examined. The embryos were cultured for 3 days. Results : Both peritoneal fluid with endometriosis and interlf:)ukin-8 were found to significantly inhibit the development of early mouse embryos. The in vitro development from 2 cells to blastocysts was suppressed in the presence of peritoneal fluid with mild, moderate or severe endometriosis (p<0.001 Fisher's exact test). lnterleukin-8 (16 and 1000 pglml) however inhibited mainly the development of the later stage embryo, from morulae to blastocysts (p<0.001 Fisher's exact test). Interestingly, pyruvate was effective in reversing the embryotoxic effects of both the peritoneal fluid with endometriosis and interleukin-8. ConClusion : The ability of pyruvate to reverse the embryotoxic effects of both peritoneal fluid.with endometriosis and inter/eukin-8 suggests that a common pathway may be involved in their actions. This provides further support to the hypothesis that interleukins mediate the embryotoxic effect of peritoneal fluid in endometriosis.